1986
DOI: 10.1002/j.1556-6978.1986.tb00681.x
|View full text |Cite
|
Sign up to set email alerts
|

Silver to Gold: The Alchemy, Potential, and Maturing of ACES and CES

Abstract: Exponential changes in Western and international society and in American and international education afford promise, opportunity, and challenges for tomorrow's counselor. Roles of counselors, counselor supervisors, and counselor educators must reflect and shape the needs and growth of populations in specific countries and throughout the world to afford timely and appropriate responses and intelligent and sensitive proactivity. Leadership in services, teaching, research, credentialing, policy, and law all seem … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1994
1994
2005
2005

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…As Lanning has noted, "We will always be driven by the master's level education we provide, but that can only continue if we prepare quality doctoral level graduates" (p. 168). This is necessary because the doctoral students who graduate from such programs with counselor education doctoral degrees will continue to advance the counseling profession on both the master's and the doctoral level (Engels & Muro, 1986).…”
mentioning
confidence: 99%
“…As Lanning has noted, "We will always be driven by the master's level education we provide, but that can only continue if we prepare quality doctoral level graduates" (p. 168). This is necessary because the doctoral students who graduate from such programs with counselor education doctoral degrees will continue to advance the counseling profession on both the master's and the doctoral level (Engels & Muro, 1986).…”
mentioning
confidence: 99%
“…psychology. and other social sciences (Engels & Muro, 1986), the literature in these related disciplines can offer some evidence of instructional methods to assist with the design and implementation of new teaching methods for counselors. Phillips (1983) suggested that law-related training is already becoming legitimized as a part of graduate training in the field of psychology.…”
Section: Instructional Methodsmentioning
confidence: 99%